2021
DOI: 10.1002/aic.17295
|View full text |Cite
|
Sign up to set email alerts
|

PtZn intermetallic nanoalloy encapsulated in silicalite‐1 for propane dehydrogenation

Abstract: Propane dehydrogenation (PDH) is one of the most effective methods to produce propylene. But the industrial Pt‐based catalysts often suffer from short‐term stability under the high temperature reaction environment (500–700°C) via sintering and coke deposition. Herein, stable PDH reaction in high propylene yield has been achieved by the confinement of Pt–Zn intermetallic alloys (IMAs) in the channels of silicalite‐1. Single‐site Zn in the MFI framework was found to play a key role on assisting and stabilizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 70 publications
(95 reference statements)
1
34
0
Order By: Relevance
“…This suggestion is based on the smaller Pt–Zn CN for the SPP-supported than for the DeAlBEA catalyst, as indicated by the EXAFS data. We further note that the literature shows that the value of CN for Pt–Zn decreases from 7 to 8 for a Pt 1 Zn 1 intermetallic alloy ,, to 4–6 for (Si-O-Zn) 4‑6 Pt-DeAlBEA and to about 4 for the (Si-O-Zn) 4‑5 Pt-SPP, consistent with the increase in the specific activity of these catalysts. It is also possible that differences in the Pt–Zn–O bond angles for Pt supported on SPP vs DeAlBEA alter the electron density on Pt in a manner that contributes to the superior activity of Pt anchored by Zn on SPP.…”
Section: Discussionsupporting
confidence: 86%
“…This suggestion is based on the smaller Pt–Zn CN for the SPP-supported than for the DeAlBEA catalyst, as indicated by the EXAFS data. We further note that the literature shows that the value of CN for Pt–Zn decreases from 7 to 8 for a Pt 1 Zn 1 intermetallic alloy ,, to 4–6 for (Si-O-Zn) 4‑6 Pt-DeAlBEA and to about 4 for the (Si-O-Zn) 4‑5 Pt-SPP, consistent with the increase in the specific activity of these catalysts. It is also possible that differences in the Pt–Zn–O bond angles for Pt supported on SPP vs DeAlBEA alter the electron density on Pt in a manner that contributes to the superior activity of Pt anchored by Zn on SPP.…”
Section: Discussionsupporting
confidence: 86%
“…[ 43 ] Propylene is a good indicator of alkene's chemisorption property on catalyst. [ 14 ] C 3 H 6 ‐TPD curves in Figure 3c directly indicate that the best PtSn/ZrM catalyst shows the weakest adsorption capacity of alkene. The easier removal of ethene product from active sites for PtSn/ZrM is therefore identified, which is important for the alleviation of ethene's deep dehydrogenation and polymerization to coke, and the following coverage of active sites.…”
Section: Resultsmentioning
confidence: 96%
“…[ 11 ] Aggregated particles with less active sites exposed on the surface and phases like PtSn 3 that are low‐active for dehydrogenation of alkanes may generate during reduction and reaction, due to the high operation temperature and different mobility of Pt and Sn. [ 12‐13 ] To maintain dehydrogenation efficiency, PtSn phase segregation and metal sintering must be minimized, [ 14‐17 ] in which the supports play an important role by regulating the geometric and electronic structure of PtSn.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Liu and co-workers prepared Pt–Zn IMA nanoparticles in silicalite-1 zeolites by introducing Pt(NH 3 ) 4 (NO 3 ) 2 and Zn(NO 3 ) 2 in the initial synthesis gel of the zeolites. 87 XANES and EXAFS measurements revealed that each Pt atom was surrounded by about seven Zn atoms, which was very close to that in Pt1Zn1 IMA with eight Zn atoms surrounding the isolated Pt atoms. The TEM measurements showed that the mean size of the Pt–Zn nanoparticles was approximately 2.4 nm and the lattice spacing of the Pt–Zn nanoparticles was 0.221 nm, which matched the interplanar distance of the (111) plane of Pt1Zn1 IMA ( P 4/ mmm ).…”
Section: Zeolite-supported Bimetal Catalystsmentioning
confidence: 53%